(3eNJUQ WHbGJ GdTYQGA (B((3GdeMOKjf(B)s - (3CHhGdHQcGJ TQa GdOjf GdeHGQc CMeO Hf GdeHGQc GdEQHdj, GdeYQha HGf GdeSJhais; (3YHO Gddg Hf eMeO GdeYJR HGddg Hf GdeJhcd Hf GdeYJUe Hf GdQTjO GdYHGSj, GHf GdeYJR, CHh GdYHGS,J (B296 (3g` s ((3CHi HQcGJ TQa GdOjf GdeHGQc s)
(3ChdgG (B:s
(3CNHGQ Hf gQeI(B: (3gh EHQGgje Hf Ydj Hf SdeI Hf gQeI GdbQTj aEfg eOM edhc Hfj eQhGfhHbi Edi BNQ CjGe GdefUhQ s
(3BNQgG (B:s
(3GdENJjGQ GdChd GdPj HYO JGQjNg ef gPG GdJGQjN, hEjGg GSCd GdJhajb, Efg LhGO cQje s
(3GHf GdeYJR gh(B: (3CHhGdYHGSs
(3YHOGddg Hf eMeO GdeYJR HGddg Hf GdeJhcd GdNdjaI GdYHGSj GdeJhai (B296 (3g```s
(3eged GdfbW CMjGfkG hajg VHW HChdgGs
(3HChdgG agQS HCSeGA TYQGA gPG GdeNJUQ s
(3hBNQgG JedcGJ heWGdYGJ hJYdjbGJ efgG SfI (B795(3g```s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs